2005
DOI: 10.1158/1078-0432.ccr-04-1936
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Multiple Myeloma Cells by a Novel IκB Kinase Inhibitor

Abstract: Involvement of nuclear factor-KB (NF-KB) in cell survival and proliferation of multiple myeloma has been well established. In this study we observed that NF-KB is constitutively activated in all human myeloma cell lines, thus confirming the previous studies. In addition, we found the phosphorylation of p65 subunit of NF-KB in addition to the phosphorylation of IKBA and the activation of NF-KB DNA binding and that various target genes of NF-KB including bcl-x L , XIAP, c-IAP1, cyclin D1, and IL-6 are up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 53 publications
2
58
0
Order By: Relevance
“…25 Briefly, approximately 1-10 Â 10 4 cells per 100 ml were cultured in 96-well plate in triplicates at 371C. Optical densities (OD) at 570 and 630 nm were measured with a multiplate reader.…”
Section: Growth Inhibition Assaymentioning
confidence: 99%
“…25 Briefly, approximately 1-10 Â 10 4 cells per 100 ml were cultured in 96-well plate in triplicates at 371C. Optical densities (OD) at 570 and 630 nm were measured with a multiplate reader.…”
Section: Growth Inhibition Assaymentioning
confidence: 99%
“…In this study, we confirmed the constitutive activation of NFkB in HTLV-1-infected T-cell and ATL cell lines and examined the effect of a novel IKK inhibitor, 2-amino-6-(2-(cyclopropylmethoxy)-6-hydroxyphenyl)-4-piperidin-4-yl nicotinonitrile (ACHP), on the growth and survival of HTLV- 19,20 Here, we demonstrate that ACHP could efficiently induce cell growth arrest and apoptotic cell death by blocking NF-kB in ATL cells. …”
Section: Introductionmentioning
confidence: 78%
“…25,26 All cell lines were cultured in RPMI 1640 medium containing 10% fetal bovine serum (FBS), streptomycin, and penicillin. Recombinant human IL-6 (Diaclone research, Besancon, France) was added at 10 ng/ml to the medium of ILKM-2, ILKM-3 and ILKM-8.…”
Section: Cell Lines and Culturementioning
confidence: 99%